AGREE II: advancing guideline development, reporting and evaluation in health care - Brouwers, Melissa C.; Kho, Michelle E.; Browman, George P.; Burgers, Jako S.; Cluzeau, Francoise; Feder, Gene; Fervers, Béatrice; Graham, Ian D.; Grimshaw, Jeremy; Hanna, Steven E.; Littlejohns, Peter; Makarski, Julie; et al. (Canadian Medical Association journal (CMAJ), 2010)
The purpose of the AGREE II is more explicitly stated. The new version of the instrument is designed to assess the quality of practice guidelines across the spectrum of health, provide direction on guideline development, and guide what specific information ought to be reported in guidelines. The four-point response scale was replaced by a seven-point response scale, in compliance with key methodologic principles of test construction. 5 A score of 1 indicates an absence of information or that the concept is very poorly reported. A score of 7 indicates that the quality of reporting is exceptional and all of the criteria and considerations articulated in the user's manual were met. A score between 2 and 6 indicates that the reporting of the AGREE II item does not fully meet criteria or considerations. As more criteria are met and more considerations addressed, item scores increase (see user's manual below). Finally, modifications, deletions and additions were made to approximately half of the original 23 items (Table 1). From McMaster University ([Melissa C. Brouwers PhD], [Michelle E. Kho], [Steven E. Hanna PhD], [Julie Makarski]); the Program in Evidence-based Care, Cancer Care Ontario (Brouwers), Hamilton, Ont.; British Columbia Cancer Agency (Browman), Victoria, BC; the Dutch Institute for Healthcare Improvement CBO and IQ Healthcare (Burgers), Radboud University Nijmegen Medical Centre, the Netherlands; St. George's University of London (Cluzeau), London, UK; the University of Bristol (Feder), Bristol, UK; Unité Cancer et Environement (Fervers), Université de Lyon - Centre Léon Bérard, Université Lyon 1, EA 4129, Lyon, France; the Canadian Institutes of Health Re search ([Ian D. Graham PhD]), Ottawa, Ont.; the Ottawa Hospital Research Institute ([Jeremy Grimshaw MBChB PhD]), Ottawa, Ont.; the National Institute for Health and Clinical Excellence (Littlejohns), London, UK; and the Can adian Partnership Against Cancer ([Louise Zitzelsberger PhD]), Ottawa, Ont. Members of the AGREE Next Steps Consortium: Dr. Melissa C. Brouwers, McMaster University and Cancer Care Ontario, Hamilton, Ont.; Dr. [George P. Browman MD MSc], British Columbia Cancer Agency, Vancouver Island, BC; Dr. [Jako S. Burgers MD PhD], Dutch Institute for Healthcare Improvement CBO, and Radboud University Nijmegen Medical Centre, IQ Healthcare, Netherlands; Dr. [Francoise Cluzeau], Chair of AGREE Research Trust, St. George's University of London, London, UK; Dr. Dave Davis, Association of American Medical Colleges, Washington, USA; Prof. Gene Feder, University of Bristol, Bristol, UK; Dr. Béatrice Fervers, Unité Cancer et Environement, Université de Lyon - Centre Léon Bérard, Université Lyon 1, EA 4129, Lyon, France; Dr. Ian D. Graham, Canadian Institutes of Health Research, Ottawa, Ont.; Dr. Jeremy Grimshaw, Ottawa Hospital Research Institute, Ottawa, Ont.; Dr. Steven E. Hanna, McMaster University, Hamilton, Ont.; Ms. Michelle E. Kho, McMaster University, Hamilton, Ont.; Prof. Peter Littlejohns, National Institute for Health and Clinical Excellence, London, UK; Ms. Julie Makarski, McMaster University, Hamilton, Ont.; Dr. Louise Zitzelsberger, Canadian Partnership Against Cancer, Ottawa, Ont.